Ka Tung grabs early lead at Amateur Open - Borneo Post, (Kuching) (BorneoPost Online, 2015)
BINTULU: Lee Ka Tung of Sibu Golf Club opened his campaign at the 46th SGA Sarawak Amateur Open golf championship at Kelab Golf Bintulu (KGB) yesterday on a bright note when he registered a gross score of 72 for a four stroke lead.